Shock transmission units in construction - Patel, Dinesh J. (ICE Publishing, 2013)
Recent earthquakes around the world have confirmed the potential for a large seismic event to cause unprecedented levels of destruction. Shock transmission units (STUs) have been used in several projects as one of the most effective instruments in preventing widespread damage from seismic activities and structural movement. 'Shock Transmission Units in Construction' explores the procurement, selection, testing, installation and maintenance processes of STUs, as well as technological developments in the field of seismic protection.